ANALISIS POLA KONSUMSI SANTRI WILAYAH AL-MAWADDAH PONDOK PESANTREN NURUL JADID - Fahrudin F Fahrudin (JOURNAL ECONOMICS AND STRATEGY, 2024)
A santri is someone who always follows their teacher wherever they go and resides with them. The consumption of santri typically revolves around dormitory fees, daily operational costs (DOP), supplements, and the everyday needs of the santri. This research aims to analyze the consumption patterns of santri in the Al-Mawaddah region of the Nurul Jadid Islamic Boarding School. The research data were obtained through observation and direct interviews with relevant parties, specifically active santri in the Al-Mawaddah region. The findings of this research indicate that the consumption patterns of santri in the Al-Mawaddah region are still excessive and not rational in terms of the use of the santri's pocket money. Keywords: Comsumption Pattern, Santri, Nurul Jadid.